Prävention von Infekten der oberen Atemwege - Voß, Sebastian; Schnakenberg, Rieke; Weckbecker, Klaus; Bleckwenn, Markus (DMW - Deutsche Medizinische Wochenschrift, 2017)
Because of its high prevalence acute respiratory diseases have a significant impact on the population. The focus of this review was the current state of knowledge for the prophylactic efficacy of: zinc, vitamin C, Echinacea preparations, garlic and carrying out physical measures. Furthermore, the benefits of pneumococcal and influenza vaccine were elicited. In the synopsis, the physical measures proved to be the most effective, cost-effective method to prevent infections. The intake of zinc, Echinacea preparations (for example: E. purpurea), vitamin C and garlic showed moderate success in the prevention of infection and must be elicited individually. Pneumococcal and annual influenza vaccines in family practice should be given furthermore accordingly topical STIKO-recommendation. Nevertheless, the prophylactic effect from influenza vaccines on usual cold illnesses is unsettled.
Keywords: Prävention; Atemwegsinfekt; Erkältung; Grippe; Impfung